New records of bird species in the Ventanilla wetlands, Callao, Peru during 2021-2024 - Rivas Blas, Rolf Aldo (2024)
The Ventanilla Wetlands Regional Conservation Area (ACRHV), is a conservation area, complementary to the natural areas protected by the state, administered by the Regional Government of Callao, Peru through the Regional Management of Natural Resources and Environmental department. It is located in the district of Ventanilla, Callao, Peru; next to this area is the Costa Azul beach and the Laguna “El Mirador Municipal” Ecological Park (LM). Within the framework of the biological monitoring of birds carried out by the administrative entity, between August 2021 and December 2023, in addition to verifiable ebird records; five new bird species were documented for the ACRHV: 1. Mareca sibilatrix (Poeppig, 1829), 2. Calidris melanotos (Vieillot, 1819), 3. Phalaropus lobatus (Linnaeus, 1758), 4. Tyrannus tyrannus (Linnaeus, 1758), and 5. Progne chalybea (Gmelin, 1789); two for Costa Azul beach: Sula neuboxii Milne-Edwards, 1882, and 2. Thalasseus sandvicensis (Latham, 1787); and two for “Laguna El Mirador”: 1. Calidris melanotos, and 2. Chlidonias niger (Linnaeus, 1758). Three of the latest records for ACRHV are boreal migratory species: T. tyrannus, P. lobatus and C. melanotos, and one of the records is the possible confirmation of a hypothetical species M. sibilatrix in Peru. The new records involve 131 bird species for ACRHV and 152 for coastal wetlands in the Callao Region.